2005
DOI: 10.1021/bi050997o
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Proximal and Distal Histidine Environment of Cytoglobin and Neuroglobin

Abstract: Cytoglobin (Cgb) and neuroglobin (Ngb) are the first examples of hexacoordinated globins from humans and other vertebrates in which a histidine (His) residue at the sixth position of the heme iron is an endogenous ligand in both the ferric and ferrous forms. Static and time-resolved resonance Raman and FT-IR spectroscopic techniques were applied in examining the structures in the heme environment of these globins. Picosecond time-resolved resonance Raman (ps-TR3) spectroscopy of transient five-coordinate heme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
70
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 40 publications
11
70
1
1
Order By: Relevance
“…However, it will be shown below that, despite the great similarity in the absorption spectra, heme pocket structures, and backbone folds, the structural dynamics of Ngb and Mb are distinct. Ligand rebinding studies of Ngb show that CO rebinding kinetics after optical excitationinduced dissociation of the CO from the heme is different from that of Mb (27,28). The results presented below demonstrate that the equilibrium structural fluctuations of Ngb are considerably slower than those of Mb.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…However, it will be shown below that, despite the great similarity in the absorption spectra, heme pocket structures, and backbone folds, the structural dynamics of Ngb and Mb are distinct. Ligand rebinding studies of Ngb show that CO rebinding kinetics after optical excitationinduced dissociation of the CO from the heme is different from that of Mb (27,28). The results presented below demonstrate that the equilibrium structural fluctuations of Ngb are considerably slower than those of Mb.…”
mentioning
confidence: 71%
“…There are two CO absorption bands at 1,932 cm Ϫ1 and 1,968 cm Ϫ1 . These bands have been called the N 3 (lower frequency) and N 0 (higher frequency) conformers, respectively, in analogy to the A 3 and A 0 bands of Mb (27,29). The significant width of the CO stretching bands of Ngb and their Gaussian shapes imply structural heterogeneity associated with each protein substate that is sensed by the CO bound to the active site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spectrum of wt-Ngb (solid curve), there are two CO bands at 1,932 cm Ϫ1 and 1,968 cm Ϫ1 . These have been called the N 3 (lower frequency) and N 0 (higher frequency) conformers, respectively, in analogy to the A 3 and A 0 bands of Mb (26)(27)(28). The significant width of the CO-stretching bands of Ngb and their Gaussian shapes implies that there is structural heterogeneity associated with each protein substate.…”
Section: Resultsmentioning
confidence: 99%
“…In neuroglobin, mutation of His to Leu in the E helix increases the ligand-binding constants, indicating that the endogenous ligand can be replaced by external ligands such as oxygen and carbonic monoxide. 46 Based on their spectroscopic analysis, Sawai et al 47 also suggested that His residue is responsible for the globin conformer structure and heme-ligand binding. These findings support experiments demonstrating that the heme domain is an important contributor to radical scavenging.…”
Section: Discussionmentioning
confidence: 99%